A framework for analysing water security of Tonle Sap Lake in the Mekong River basin: Flow, volume, inundation, productivity and livelihoods - Sithirith, Mak (Wiley, 2024)
Water is a scarce resource globally, and a water shortage worldwide would cause water security. Although there is plenty of literature studying water security, many discuss water security concerning water quality that is harmful to human health, some on the floods and droughts which destroy agriculture and livelihoods of people, and others on water war or water conflict in transboundary river basin; but little discusses water security concerning changing river flow, volume, inundation, productivity and livelihoods in the river–lake system (RLS). Thus, this paper studies the RLS to examine how changes in river flows and the volumes of the water in the RLS would affect the inundation and productivity of the RLS and, later, the livelihoods of river–lake people (RLP). In answering this question, the article undertakes the literature review and the case study of Tonle Sap Lake (TSL) in Cambodia to examine this form of water security. The paper concludes that the RLS has a close relationship between the flow, volume, inundation and productivity of fisheries and people's livelihoods. The hydropower dams, urban development and climate change cause the disconnectivity and the discontinuity of the river–lake flow, volume and inundation, undermining the productivity of fisheries and livelihoods of river–lake-dependent communities. There is a strong need for cooperation and coordination between riparian states in the Mekong River Basin (MRB) to maintain the secured flow and volume in the Mekong River (MR) and TSL and protect the livelihoods of RLP.